Debt Relief for Low-Income Countries : The HPIC initiative (Revised 1997). (Pamphlet Series, 1999)
This paper describes the Heavily Indebted Poor Countries (HIPC) Initiative and suggests that it should enable HIPCs to exit from the debt-rescheduling process. It argues that implementation of the Initiative should eliminate debt as an impediment to economic development and growth and enable HIPC governments to focus on the difficult policies and reforms required to remove the remaining impediments to achieving sustainable development. The paper describes the implementation of the Initiative through the end of September 1998.